2021
DOI: 10.1097/01.hjh.0000747300.64702.c6
|View full text |Cite
|
Sign up to set email alerts
|

Central Integration of Left Versus Right Baroreceptor Afferent Input in Female Spontaneously Hypertensive Rats

Abstract: Objective: Neuromodulation of blood pressure using baroreflex activation therapy is an effective means to control hypertension in resistant hypertensive patients. In a genetic rat model of essential hypertension, the spontaneously hypertensive rats (SHRs); we were able to demonstrate in male rats that preferential central integration of left baroreceptor afferent input exists relative to that of the right afferents. It remains unknown whether laterality also influences baroreflex responses in femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 0 publications
2
6
3
Order By: Relevance
“…Unexpectedly, peak reflex depressor responses to left and right ADN stimulation and the immediacy of those responses were relatively similar, hence suggesting that central integration of left versus right aortic baroreceptor afferent input is not differentially regulated in female SHRs. These findings notably contrast with our previous observation of a left-sided dominance in the expression of aortic baroreflex function in male SHRs [22] and normotensive rats of either sex [21]. Together, these findings indicate a sexual dimorphism in the processing of the aortic baroreflex relative to male SHRs and the loss of functional asymmetry that would otherwise be observed under normotensive conditions in females.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Unexpectedly, peak reflex depressor responses to left and right ADN stimulation and the immediacy of those responses were relatively similar, hence suggesting that central integration of left versus right aortic baroreceptor afferent input is not differentially regulated in female SHRs. These findings notably contrast with our previous observation of a left-sided dominance in the expression of aortic baroreflex function in male SHRs [22] and normotensive rats of either sex [21]. Together, these findings indicate a sexual dimorphism in the processing of the aortic baroreflex relative to male SHRs and the loss of functional asymmetry that would otherwise be observed under normotensive conditions in females.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, our studies have shown that normotensive rats of either sex tend to exhibit a left-sided dominance in the central integration of baroreceptor afferent input; however, in females, baroreflex processing of the left or bilateral baroreceptor afferent input appears to contribute to higher reflex depressor responses compared with males [21]. Using the same experimental approach, we have also identified an identical functional asymmetry in aortic baroreflex function in male SHRs [22]. However, it remains undetermined if the hypertensive state would alter the expression of laterality in female SHRs.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations